Acceptability of cell substrates for production of biologicals : report of a WHO study group, meeting held in Geneva from 18 to 19 November 1986 - WHO Study Group on Biologicals; World Health Organization (Geneva : World Health Organization, 1987)
A brief yet highly significant analysis of issues associated with the use of eukaryotic and prokaryotic cells in the production of biologicals. The report considers two main types of issues: first, the acceptability of developing a biological product in a new cell system when the same generic product is already being manufactured by an approved method, and second, the degree of risk associated with certain classes of possible contaminants in the product. These include heterogeneous contaminating DNA, viruses, and transforming poteins. For each contaminant, the report describes and analyses the potential risks to humans and, where appropriate, categorizes and classifies these risks. The report also advocates basic principles of manufacturing and testing that can help minimize the likelihood of risks to human recipients of products manufactured in continuous cell lines.
1. Background and introduction -- 2. Issues considered by the Study Group -- 3. Discussion and conclusions -- 4. Recommendations -- 5. Acknowledgements -- Annexes
Keywords: Vaccines; Cell Line; Pharmacology, Toxicology and Clinical Technology